2018
DOI: 10.1515/jpem-2018-0210
|View full text |Cite
|
Sign up to set email alerts
|

Does the risk of arterial hypertension increase in the course of triptorelin treatment?

Abstract: Although the etiology of this adverse event is not known and only some hypotheses can be made, clinicians should be aware that arterial hypertension might appear during triptorelin treatment in childhood with CPP. Therefore, they should routinely monitor the arterial blood pressure of patients under treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…This was also previously reported in 2016 [23]. Additionally, two cases of arterial hypertension following treatment with triptorelin, which resolved after discontinuation of GnRHa, were reported in 2020 and 2019 [24,25]. A recent study of blood pressure changes following induction of GnRHa therapy in 15 transgender male patients [26 ] found a significant but not hypertensive rise of diastolic blood pressure.…”
Section: Safety/adverse Events Associated With Gonadotropin-releasing...supporting
confidence: 71%
“…This was also previously reported in 2016 [23]. Additionally, two cases of arterial hypertension following treatment with triptorelin, which resolved after discontinuation of GnRHa, were reported in 2020 and 2019 [24,25]. A recent study of blood pressure changes following induction of GnRHa therapy in 15 transgender male patients [26 ] found a significant but not hypertensive rise of diastolic blood pressure.…”
Section: Safety/adverse Events Associated With Gonadotropin-releasing...supporting
confidence: 71%
“…In both cases, re-exposition to the offending drug was not performed. Finally, Palma et al also very recently report a girl with CPP and arterial HTN during treatment with Triptorelin, HTN that subsided once Triptorelin was interrupted (6).…”
Section: Discussionmentioning
confidence: 98%
“…Triptorelin is a widely used drug with few reported adverse effects, such as erythema, bruising, pain, sterile abscesses, menopausal-like symptoms, and anaphylaxis (2, 3). So far secondary arterial hypertension (HTN) has been reported in only 3 patients with CPP (46).…”
Section: Introductionmentioning
confidence: 99%
“…High blood pressure was only present in 3 participants of the GnRHa/ GH group, which was similar in the GH-only and AGA groups. Two case reports have described transient arterial hypertension during GnRHa treatment (31,32). Both cases showed that blood pressure returned to normal values after cessation of GnRHa treatment.…”
Section: Discussionmentioning
confidence: 99%